2018
DOI: 10.1101/345942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genomic basis of colour pattern polymorphism in the harlequin ladybird

Abstract: 2Many animal species are comprised of discrete phenotypic forms. Understanding the genetic mechanisms generating and maintaining such phenotypic variation within species is essential to comprehending morphological diversity. A common and conspicuous example of discrete phenotypic variation in natural populations of insects is the occurrence of different colour patterns, which has motivated a rich body of ecological and genetic research [1][2][3][4][5][6] . The occurrence of dark, i.e. melanic, forms, displayin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(41 reference statements)
0
2
0
1
Order By: Relevance
“…In contrast to a relative paucity of field data, and a relatively lack of progress in establishing baseline theory, advances in DNA sequencing technology have meant that knowledge on the genetics of colour polymorphism is advancing rapidly. As hypothesised, in the still relatively few supergenes that have been fully characterised, the discrete phenotypes are maintained due to close physical proximity of the gene(s) and/or tight linkage (Joron et al 2011; Kunte et al 2014; Gautier et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to a relative paucity of field data, and a relatively lack of progress in establishing baseline theory, advances in DNA sequencing technology have meant that knowledge on the genetics of colour polymorphism is advancing rapidly. As hypothesised, in the still relatively few supergenes that have been fully characterised, the discrete phenotypes are maintained due to close physical proximity of the gene(s) and/or tight linkage (Joron et al 2011; Kunte et al 2014; Gautier et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Arquiteturas genéticas de polimorfismos implicando apenas genes isolados também já foram identificadas, quer devido a mutações pontuais 30,31 , quer pela ocorrência de variantes estruturais mais complexas, como a inserção de elementos móveis do genoma 32,33 ou inversões localizadas 34,35 . Nestes casos, a correlação entre múltiplos fenótipos em cada morfo é normalmente explicada por efeitos pleiotrópicos da mutação causal.…”
Section: Revista De Ciência Elementarunclassified
“…The thermal phenotypic plasticity of H. axyridis is physiologically based on melanization; different melanic patterns are presented as an orange background with various dark (melanin) spots (Tan, 1946; Michie et al ., 2010; Knapp & Nedvěd, 2013; Sun et al ., 2018a, b); and recent studies identified the gene pannier intron drives diversification of intraspecific color patterns of elytra ground H. axyridis adults (Ando et al ., 2018; Gautier et al ., 2018). However, compared with adult stage, the pupal stage normally lasts for a short time (about 3 d under 25 °C rearing conditions, based on the authors’ preliminary experiments), and individuals at this stage find it nearly impossible to move (Koch, 2003); thereafter H. axyridis have to cope with threats, including thermal threats, quickly, and fully rely on their body (cannot move to escape).…”
Section: Introductionmentioning
confidence: 99%